Impact of magnetization state on the corrosion of sintered Nd–Fe–B magnets for e‐motor applications. Issue 9 (2nd April 2013) - Moore, M.; Sueptitz, R.; Gebert, A.; Schultz, L.; Gutfleisch, O.
<x xml:space="preserve">Abstract</x> We have created an accelerated corrosion environment for sintered Nd–Fe–B magnets in e‐motor applications. E‐motor working conditions are complex, and standard magnet corrosion tests only cover a small subset of possible parameters (e.g., samples are usually tested in the demagnetized state). In this work magnetized and demagnetized sintered Nd–Fe–B magnets were placed in gearbox oil, and exposed to temperature cycles (θmax = 130 °C) using an autoclave. Beforehand the magnets were pre‐immersed in saturated water‐based salt solution to account for water and de‐icing salt that might interfuse gearbox oil over time. The corrosive behavior was studied for two commercial magnet grades, "high grade" (8.9 wt% dysprosium) and "low grade" (3.1 wt% dysprosium); and monitored by weight loss, structural analysis (scanning electron microscopy and energy dispersive X‐ray) as well as magnetic characterization. The magnetized samples corroded significantly faster than their demagnetized counterparts. Strong differences in the corrosion rates of the "low grade" and "high grade" material are discussed. We concluded that the magnetization state is one key parameter that needs to be considered in corrosion tests for e‐motor applications.